Chemical Characterization of Lodoicea maldivica Fruit. Issue 8 (6th July 2017) - Sebastiani, Bartolomeo; Giorgini, Martino; Falcinelli, Stefano
Abstract : In the present study, we report the attempt to characterize the chemical composition of fruit kernel of Lodoicea maldivica coco nucifera palm (commonly named as 'Coco de mer') by gas chromatographic method. The analysis was performed by HS‐SPME and GC/MS techniques to determine volatile aroma, sterol, and fatty acid composition profiles in the internal and external pulp of two distinct coconuts. Although no qualitative differences in flavour composition were observed between the two analysed coconuts and the relative two pulp parts, variations in the abundance levels of the prominent compounds have been recorded. The averaged quantity of total phytosterols, resulting from the two analysed 'Coco de mer' samples, was almost constant in both kernels coconut, being 24.5 μg/g (of dry net matter) for the external, and 26.9 μg/g (of dry net matter) for the internal portion. In both coconuts, the fatty acid pattern composition was characterized by seven saturated acids ranged from C14:0 (myristic) to C20:0 (arachidic) and two monounsaturated acids, the palmitoleic (C16:1, ω 7) and the oleic (C18:1, ω 9). Palmitic acid (C16:0) was the predominant one with an average contribution of about 49.0%, followed by pentadecanoic 16.5%, stearic (C18:0) 11.6%, and myristic (C14:0) 9.9% acids in all two examined kernel portions. Abstract :